An interdisciplinary program for familiar faces with chronic pain visiting the emergency department—randomized controlled trial. Issue 1 (22nd January 2022) - Shergill, Yaadwinder; Poulin, Patricia; Rice, Danielle; Rash, Joshua A.; Hebert, Guy; Tennant, Emily; Khoo, Eve‐Ling; Romanow, Heather; Singer, Lesley; Jarvis, Virginia; Nathan, Howard; Smyth, Catherine
Abstract: Objectives: To evaluate the effect of a collaborative interdisciplinary pain assessment program on pain and health‐related quality of life among individuals with chronic pain who frequently visit the emergency department (ED). Methods: Individuals with chronic pain who frequented the ED (ie, ≥8 visits within the previous 12 months) were randomly assigned to a collaborative chronic pain management program or treatment as usual. Primary outcomes were change in physical function and visits to the ED from baseline to 12 months using validated measures. Secondary measures included physical and emotional functioning, insomnia, health‐related quality of life, risk of aberrant opioid use, and health care use. Mixed model analyses of variances were used to evaluate intervention effectiveness among the whole sample (ie, using intention to treat principles) and individuals who completed more than 50% of follow‐up assessments. Results: One hundred participants were assessed for eligibility and 46 patients were enrolled with 24 being randomized to intervention and 22 to treatment as usual (TAU). Eleven of the 24 patients randomized to the intervention were lost to follow‐up and 3 withdrew participation. Two of the 22 patients randomized to TAU were lost to follow‐up, and 7 withdrew. Although patients assigned to the intervention improved more rapidly on measures of pain and health related quality of life, both groups had similar improvements overall between baseline to 12 months. Average pain intensity reduction (numeric rating scale [SE]) was 4.63 (0.40) in the intervention and 4.82 (0.53) in the treatment as usual at the 12‐month follow‐up. A significant group × time interaction was present for risk of aberrant opioid use, with individuals in the intervention group reporting greater improvement in risk of aberrant opioid use by 12‐month follow‐up. Conclusion: Participation in an interdisciplinary program may accelerate improvements in pain‐ and health‐related quality of life and reduce risk of aberrant opioid use to manage pain and related distress. Further research is needed to better understand and address barriers to engagement in chronic pain care.